Evaluating the effects of a biopesticide on populations of the variegated grasshopper, Zonocerus variegatus - Thomas, M.B.; Langewald, J.; Wood, S.N. (1997)
A field trial was conducted to investigate the efficacy of an oil formulation of the fungal entomopathogen, Metarhizium flavoviride, for control of the variegated grasshopper, Zonocerus variegatus. The results of the trial showed a significant reduction in grasshopper populations following spray application compared with non-treated controls. 2. Further studies revealed that there was significant movement of insects into and out of the treated plots during the course of the experiment, and that the pathogen spray residue remained infective for several days after application. 3. To help interpret these data and link them more closely to the basic population counts, insect-pathogen models were developed which accounted for the effects of secondary pick up of spores, insect movement and mortality on disease levels observed in the field. These revealed that contact with spores from the spray residue was an important route of infection for insects moving into the treated areas after spraying. They also revealed that there was an increase in disease incubation periods in the field compared with the laboratory; this slowed mortality rates. 4. Overall, the combination of laboratory, field and theoretical studies suggested that the total impact of the M. fiavoviride-based biopesticide was very high. This combination of techniques revealed considerably more information than the indi- vidual indicators of efficacy commonly used to assess biopesticide applications. As such, this study demonstrates how basic ecological approaches can be of value in an applied context, helping to provide a link between laboratory and field studies, and aiding the interpretation of complex field trial results